Oxygen Plasma Induced Hierarchically Structured Gold Electrocatalyst for Selective Reduction of Carbon Dioxide to Carbon Monoxide - Koh, Jai Hyun; Jeon, Hyo Sang; Jee, Michael Shincheon; Nursanto, Eduardus Budi; Lee, Hyunjoo; Hwang, Yun Jeong; Min, Byoung Koun (American Chemical Society, 2015)
Electrochemical reduction of CO2 into C1 products with high energy density has attracted attention due to the demands for renewable energy sources. Herein, we demonstrate a selective electrocatalytic CO2 reduction system where the cathode consists of hierarchically structured Au islands catalysts. To be more specific, the Au islands were prepared by oxygen plasma treatment on the Au foil to increase the current density for the selective production of carbon monoxide with over 95% of faradaic efficiency. Faradaic efficiency, production rate, and the onset potential for CO2 reduction were significantly improved by the expanded surface area compared with a polycrystalline Au electrode. Furthermore, the performance of CO2 reduction to CO was enhanced by adding ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate) which has high CO2-capture ability and catalytic activity. On the other hand, the rate-determining step of the Au electrode for the CO production determined by Tafel plots was found to be consistent with the initial one electron transfer step to form the surface-adsorbed CO2 intermediates regardless of the application of hierarchically structured catalyst and ionic liquid in the CO2 reduction system.
Keywords: ELECTROCHEMICAL REDUCTION; CO2 REDUCTION; ENHANCED ACTIVITY; CONVERSION; CATALYSTS; ELECTRODE; POTENTIALS; EFFICIENCY